2011
DOI: 10.1055/s-0030-1270531
|View full text |Cite
|
Sign up to set email alerts
|

Fibular Free Flap with Arteria Peronea Magna: The Role of Preoperative Balloon Occlusion

Abstract: The free fibular osteocutaneous flap is a commonly used donor for reconstruction of mandibular defects. Vascular abnormalities and leg trauma are relative contraindications to the use of a fibular free flap. Peroneal arteria magna (PAM) is one such vascular abnormality that may preclude the use of the graft due to the high risk of lower-limb ischemia. Lower-limb angiography is the standard for assessing the lower-limb vascular anatomy; however, the indications remain controversial. Although balloon occlusion h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Preoperative angiography of both legs should be carried out routinely to specify the distribution of blood vessels in the donor area. Anatomic variations where peroneal artery is absent or is the dominant artery supplying the leg and foot (known as peroneal arteria magna) should be detected in advance, otherwise harvest failure or ischemia of the distal limb would happen [7]. Preoperative angiography is more necessary for patients with comorbidities.…”
Section: Donor-site Morbiditiesmentioning
confidence: 99%
“…Preoperative angiography of both legs should be carried out routinely to specify the distribution of blood vessels in the donor area. Anatomic variations where peroneal artery is absent or is the dominant artery supplying the leg and foot (known as peroneal arteria magna) should be detected in advance, otherwise harvest failure or ischemia of the distal limb would happen [7]. Preoperative angiography is more necessary for patients with comorbidities.…”
Section: Donor-site Morbiditiesmentioning
confidence: 99%
“…Most variation results from non-standard arterial division, aplasia, or hypoplasia. However, these variations are extremely rare for the peroneal artery [ 6 ]. Although these anomalies may still be encountered by reconstructive surgeons, radiologists, and other lower limb surgeons, if one is vigilant.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Other novel approaches have been cited in the literature: one case report detailed the use of preoperative balloon occlusion to assess distal limb ischemia in the setting of PAM. 14 …”
Section: Discussionmentioning
confidence: 99%
“…4 Other novel approaches have been cited in the literature: one case report detailed the use of preoperative balloon occlusion to assess distal limb ischemia in the setting of PAM. 14 For surgeons who opt to use preoperative imaging, the knowledge of a PAM may alter the surgical plan. A systematic review reported that in 21 of the 28 cases of a dominant PA in FFF, surgeons altered their plan and did not to utilize the affected leg in 17 of 21 patients.…”
Section: Discussionmentioning
confidence: 99%